Bacterial membrane permeability of antimicrobial polymethacrylates: Evidence for a complex mechanism from super-resolution fluorescence imaging. (May 2020) - Michl, Thomas D.; Hibbs, Ben; Hyde, Lauren; Postma, Almar; Tran, Dung Thuy Thi; Zhalgasbaikyzy, Aigerim; Vasilev, Krasimir; Meagher, Laurence; Griesser, Hans J.; Locock, Katherine E.S.
Abstract: Amphiphilic polymers bearing cationic moieties are an emerging alternative to traditional antibiotics given their broad-spectrum activity and low susceptibility to the development of resistance. To date, however, much remains unclear regarding their mechanism of action. Using functional assays (ATP leakage, cell viability, DNA binding) and super-high resolution structured illumination microscopy (OMX-SR) of fluorescently tagged polymers, we present evidence for a complex mechanism, involving membrane permeation as well as cellular uptake, interaction with intracellular targets and possible complexation with bacterial DNA. Statement of Significance: This manuscript details the first study to systematically and directly investigate the mechanism of action of antimicrobial polymers, using super-resolution fluorescence imaging as well as functional assays. While many in the field cite membrane permeation as the sole mechanism underlying the activity of such polymers, we present evidence for multimodal actions including high cellular uptake and interaction with intracellular targets. It is also the first report to show competitive binding of antimicrobial polymers with bacterial DNA in a dose-dependent manner. Graphical abstract: Image, graphical abstract